2021
DOI: 10.3390/ijerph18168462
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Influencing Factors of Transfer Passenger Flow of Urban Rail Transit: A New Approach Based on Nested Logit Model Considering Transfer Choices

Abstract: With the continuous improvement of the operation line network of urban rail transit, analyzing influencing factors of transfer passenger flow of urban rail transit is critical to improve the transfer demand analysis of urban rail transit. Using data collected from questionnaires, transfer passenger flow surveys and smart cards, this study proposes an approach base on nested logit passenger flow assignment model considering transfer choice behaviours of passengers. The transfer passenger flow at seven transfer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The different structures of an urban road network have a deep impact on the mode of transportation [31]. Many residents choose to travel by metro [32]. For health reasons, some residents may choose to walk [33].…”
Section: Situation Of Nanjing Metromentioning
confidence: 99%
“…The different structures of an urban road network have a deep impact on the mode of transportation [31]. Many residents choose to travel by metro [32]. For health reasons, some residents may choose to walk [33].…”
Section: Situation Of Nanjing Metromentioning
confidence: 99%
“…In order to analyze the influencing factors of urban rail transit transfer flows, a method based on a nested logit flow distribution model was proposed to derive the transfer flows at seven transfer stations in Nanjing, China, using questionnaire surveys, transfer flow surveys, and smartcard data, taking into account the transfer choice behavior of passengers. The results showed that the relationship between the transfer passenger flow, and the economic, geographical and transport location is unclear [15]. To solve the problem of overcrowding at transfer stations during peak hours, Yin JT put forward a mathematical formula aiming to minimize the degree of overcrowding at stations during peak hours to generate the best-coordinated train schedule synchronously and use ALNS algorithm to find the best solution [16].…”
Section: Introductionmentioning
confidence: 99%
“…e Chinese government formally put forward the goal of 'carbon neutralization and carbon compliance' at the 75 th United Nations General Assembly in 2020 and strongly developed a low-carbon economy to reduce greenhouse gas emissions. Among many greenhouse gas emission pathways, transportation accounts for more than 20% of the total greenhouse gas emission [2][3][4][5], and the carbon emission of ground transportation is much higher than that of air transportation [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%